THE IMPACT OF DIGITAL TRANSFORMATION, WORK-LIFE BALANCE, AND DIVERSITY POLICIES ON EMPLOYEE PRODUCTIVITY IN START-UPS IN JAKARTA - Kowey, Wylda Olivia; Leuhery, Ferdy; Hiariey , Harvey; Sijabat , Asiani (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study investigates the impact of digital transformation, work-life balance, and diversity policies on employee productivity in start-ups in Jakarta. Employing a quantitative research design, data were collected from 185 respondents using a Likert scale (1–5) and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS) 3. The results reveal that digital transformation, work-life balance, and diversity policies significantly and positively affect employee productivity, with the model explaining 65% of the variance in productivity. Digital transformation emerged as the strongest predictor, underscoring the critical role of technological integration in start-ups. Work-life balance and diversity policies also significantly contribute to productivity, highlighting the importance of fostering employee well-being and inclusivity. These findings offer theoretical insights and practical recommendations for optimizing productivity in dynamic and competitive start-up environments.